Social compensation, retraining, shorter working hours? Citizen's social policy priorities for the age of automation - Marius R. Busemeyer; Tobias Tober (University of Konstanz, Cluster of Excellence "The Politics of Inequality", Das Progressive Zentrum e.V., 2021)
Robotization, automation and digitalization are transforming labor markets around the globe - more than ever now that a pandemic has shown that our economy is fragile and dependent on specific, often unrecognized jobs. What do citizens expect from their governments in response? Our study of 24 OECD countries shows deep concerns about tech-related job risks. But technological change also raises many positive expectations. Education and training measures for those affected by tech-related change are greeted with widespread approval. Disadvantaged workers, however, would prefer short-term compensations for the potential loss of their jobs. Governments are advised to strike a balance between making social investments in the digital knowledge economy and awarding social transfers. – – Robotisierung, Automatisierung und Digitalisierung verändern die Arbeitsmärkte weltweit - umso mehr, seit die Pandemie die Abhängigkeit unserer Wirtschaft von bestimmten Berufszweigen aufgezeigt hat. Welche Antworten auf diesen Wandel erwarten die Bürger*innen von ihren Regierungen? Unsere Studie in 24 OECD-Ländern zeigt: Es herrscht große Besorgnis über technologiebedingte Arbeitsplatzrisiken, der technologische Wandel weckt aber auch Hoffnungen. Aus- und Fortbildungsmaßnahmen stoßen auf breite Zustimmung. Diejenigen, deren Arbeitsplatz aber konkret in Gefahr ist, erwarten für die Zeit der Arbeitslosigkeit vor allem kurzfristige, materielle Unterstützung. Die Politik sollte darum eine Balance zwischen notwendigen Investitionen in die digitale Wissensökonomie und sozialen Transferleistungen finden.
urn:nbn:de:bsz:352-2-rnmk8cdmve6f2
Keywords: 320